2007
DOI: 10.2174/092986607782110239
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Chimeric Synthetic Peptide in the Development of a Serologic Method for the Diagnosis of Hepatitis G Virus Infection

Abstract: New putative antigenic peptides corresponding to the N- and C-terminal of the E2 envelope protein of GBV-C/HGV were synthesized using solid-phase chemistry. The antigens were obtained in linear and chimeric forms with the main aim of improving the sensitivity of the enzyme immunoassays. Furthermore, CD and FTIR have been used in conjunction to characterize their conformational changes showing that the chimeric peptide presents a more ordered secondary structure than its parent peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Unlike HCV, which elicits antibodies to several viral proteins during viraemia that usually persist throughout infection (Baumert et al , 2000), GBV-C/HGV antibodies are not generally detected during viraemia, although some studies have reported the detection of anti-GBV-C/HGV peptide reactivity (Fernandez-Vidal et al , 2007; Gomara et al , 2010; Pilot-Matias et al , 1996b; Schwarze-Zander et al , 2006; Tan et al , 1999; Van der Bij et al , 2005; Xiang et al , 1998). Following clearance of GBV-C/HGV viraemia, most individuals develop conformation-dependent antibodies to the envelope glycoprotein E2, and thus E2 antibody serves as a marker of prior infection (Barnes et al , 2007; Gutierrez et al , 1997; McLinden et al , 2006; Nakatsuji et al , 1992; Pilot-Matias et al , 1996a; Tacke et al , 1997; Tanaka et al , 1998).…”
Section: Virologymentioning
confidence: 99%
“…Unlike HCV, which elicits antibodies to several viral proteins during viraemia that usually persist throughout infection (Baumert et al , 2000), GBV-C/HGV antibodies are not generally detected during viraemia, although some studies have reported the detection of anti-GBV-C/HGV peptide reactivity (Fernandez-Vidal et al , 2007; Gomara et al , 2010; Pilot-Matias et al , 1996b; Schwarze-Zander et al , 2006; Tan et al , 1999; Van der Bij et al , 2005; Xiang et al , 1998). Following clearance of GBV-C/HGV viraemia, most individuals develop conformation-dependent antibodies to the envelope glycoprotein E2, and thus E2 antibody serves as a marker of prior infection (Barnes et al , 2007; Gutierrez et al , 1997; McLinden et al , 2006; Nakatsuji et al , 1992; Pilot-Matias et al , 1996a; Tacke et al , 1997; Tanaka et al , 1998).…”
Section: Virologymentioning
confidence: 99%
“…The syntheses of peptides E2 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), E2 (354-363) as well as a chimeric sequence were previously described [16][17][18]. Physicochemical properties of these peptides, such as net charge at pH 7.4, isoelectric point and Grand Average of Hydropathicity (GRAVY) were predicted using the Expasy-ProtParamprogram [27].…”
Section: Peptide Syntheses and Characterizationmentioning
confidence: 99%
“…All the studied peptides are positively charged at pH 7.4, although the E2 (354-367) peptide has a net charge slightly more positive (higher isoelectric point) than the others. The GRAVY of the E2 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) peptide is negative, indicating its hydrophilicity. However, E2 (354-363) is highly hydrophobic as compared with the other two peptides.…”
Section: Peptide Syntheses and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations